A Review on Human Respiratory Modeling - Ghafarian, Pardis (Tanaffos, 2016)
Input impedance of the respiratory system is measured by forced oscillation technique (FOT). Multiple prior studies have attempted to match the electromechanical models of the respiratory system to impedance data. Since the mechanical behavior of airways and the respiratory system as a whole are similar to an electrical circuit in a combination of series and parallel formats some theories were introduced according to this issue. It should be noted that, the number of elements used in these models might be less than those required due to the complexity of the pulmonary-chest wall anatomy. Various respiratory models have been proposed based on this idea in order to demonstrate and assess the different parts of respiratory system related to children and adults data. With regard to our knowledge, some of famous respiratory models in related to obstructive, restrictive diseases and also Acute Respiratory Distress Syndrome (ARDS) are reviewed in this article.